THE ROLE OF INDIVIDUAL ATTITUDES ON BIKESHARING MODE CHOICE AS METRO TRANSIT USERSâ EGRESS MODE - Pratita Dewayanto, Damar
Bikesharing scheme is considered as one of concepts to fill in the gap of last mile stage on public transport trip chain. Understanding the potential demand for choosing bikesharing as metro transit users’ egress mode needs to be undertaken. This study focusses on investigating determinant factors affecting potential users (metro transit users) to choose bikesharing as their egress mode in Yogyakarta Urbanized Area (YUA). Three metro transit stations are located within this area which composed of Yogyakarta Station, Lempuyangan Station, and Maguwo Station. All metro transit users (KRL Yogyakarta – Solo and KRD Prameks) who travel to YUA and alight to those stations are determined as the unit analysis for this study. An Integrated Choice and Latent Variable (ICLV) on Hybrid Choice Model (HCM) framework is specified as a method analysis to estimate bikesharing mode choice model. By using ICLV approach, the estimation consists of three model, namely the structural equation model, measurement equation model, and mode choice model. Cross-sectional field survey was determined as data collection method, which consist of four sections (socio-economic section, travel-related section, attitudinal statements toward cycling activities, and stated preference experiment). Hence, 1528 observations were collected through cross-sectional field survey. Firstly, the latent variable of attractiveness to cycle (ATTCYC) and cycling experience attitude (CYCEX) were identified through exploratory factor analysis. Furthermore, the results of structural equation model show that female passenger is significantly identified as negative effect to attractiveness to cycle attitude. The results of measurement equation model show that all estimated parameter’s values and signs are found significant as expected from the earlier findings. The choice model results show the latent variable of attractiveness to cycle (ATTCYC), and all explanatory variable such as integrated payment, number of bikes information apps, and lesser rental tariff are found significant and have positive effect towards bikesharing mode choice, whereas the walking distance from docking station to destination point is found negative effect. However, latent variable of cycling experience attitude (CYCEX) has found as non-significant determinant factor towards bikesharing mode choice.